Efficient production of androstenedione by repeated batch fermentation in waste cooking oil media through regulating NAD+/NADH ratio and strengthening cell vitality of Mycobacterium neoaurum. (May 2019) - Zhou, Xiuling; Zhang, Yang; Shen, Yanbing; Zhang, Xiao; Xu, Shuangping; Shang, Zhihua; Xia, Menglei; Wang, Min
Highlights: Type II NADH dehydrogenase firstly was enhanced in Mycobacterium neoaurum . NAD + /NADH ratio and cells viability were improved after enhancing NDH-II. The waste cooking oil was used as cosolvent on phytosterol biotransformation. Tween 80-WCO-water media system can effectively improve conversion rate. AD productivity increased by 13.75 times through repeated batch fermentation. Abstract: The bioprocess for producing androstenedione (AD) from phytosterols by using Mycobacterium neoaurum is hindered by nicotinamide adenine dinucleotides (NAD + and NADH) ratio imbalance, insoluble substrate, and lengthy biotransformation period. This study aims to improve the efficiency of AD production through a combined application of cofactor, solvent, and fermentation engineering technologies. Through the enhanced type II NADH dehydrogenase (NDH-II), the NAD + /NADH ratio and ATP levels increased; the release of reactive oxygen species decreased by 42.32%, and the cell viability improved by 54.17%. In surfactant-waste cooking oil-water media, the conversion of phytosterol increased from 23.92% to 94.98%. Repeated batch culture successfully reduced the biotransformation period from 30 to 17 days, the productivity was 13.75 times more than the parent strain. This study is the first to improve the productivity of AD by enhancing NDH-II and provides a new strategy to increase the accumulation of NAD + -dependent metabolites during biotransformation.